HEADLESS, a WUSCHEL homolog, uncovers novel aspects of shoot meristem regulation and leaf blade development in Medicago truncatula - Meng, Yingying (Journal of experimental botany, 2019)
The formation and maintenance of the shoot apical meristem (SAM) are critical for plant development. However, the underlying molecular mechanism of regulating meristematic cell activity is poorly understood in the model legume Medicago truncatula. Using forward genetic approaches, we identified HEADLESS (HDL), a homolog of Arabidopsis WUSCHEL, required for SAM maintenance and leaf development in M. truncatula. Disruption of HDL led to disorganized specification and arrest of the SAM and axillary meristems, resulting in the hdl mutant being locked in the vegetative phase without apparent stem elongation. hdl mutant leaves are shorter in the proximal-distal axis due to reduced leaf length elongation, which resulted in a higher blade width/length ratio and altered leaf shape, uncovering novel phenotypes undescribed in the Arabidopsis wus mutant. HDL functions as a transcriptional repressor by recruiting MtTPL through its conserved WUS-box and EAR-like motif. Further genetic analysis revealed that HDL and STENOFOLIA (STF), a key regulator of M. truncatula lamina outgrowth, act independently in leaf development although HDL could recruit MtTPL in the same manner as STF does. Our results indicate that HDL has conserved and novel functions in regulating shoot meristems and leaf shape in M. truncatula, providing new avenues for understanding meristem biology and plant development